Abdominal muscle activity during breathing in different postures in COPD “Stage 0” and healthy subjects - Mesquita Montes, António (2019)
This study aims to evaluate the effect of different postures on the abdominal muscle activity during breathing in subjects "at risk" for the development of chronic obstructive pulmonary disease (COPD) and healthy. Twenty-nine volunteers, divided in "At Risk" for COPD (n=16; 47.38±5.08years) and Healthy (n=13; 47.54±6.65years) groups, breathed at the same rhythm in supine, standing, tripod and 4-point-kneeling positions. Surface electromyography was performed to assess the activation intensity of rectus abdominis, external oblique and transversus abdominis/internal oblique (TrA/IO) muscles, during inspiration and expiration. From supine to standing, an increased activation of all abdominal muscles was observed in "At Risk" for COPD group; however, in Healthy group, TrA/IO muscle showed an increased activation. In both groups, the TrA/IO muscle activation in tripod and 4-point kneeling positions was higher than in supine and lower than in standing. Subjects "at risk" for the development of COPD seemed to have a specific recruitment of the superficial layer of ventrolateral abdominal wall for the synchronization of postural function and mechanics of breathing.